High Throughput Multiplex SNP-analysis in Chronic Obstructive Pulmonary Disease and Lung Cancer - Elek, Zsuzsanna; Kovács, Zsuzsanna; Keszler, Gergely; Szabó, Miklós; Csanky, Eszter; Luo, Jane; Guttman, András; Rónai, Zsolt (Current Molecular Medicine, 2020)
Background: A number of human inflammatory diseases and tumors have been shown to cause alterations in the glycosylation pattern of plasma proteins in a specific manner. These highly variable and versatile post-translational modifications finetune protein functions by influencing sorting, folding, enzyme activity and subcellular localization. However, relatively little is known about regulatory factors of this procedure and about the accurate causative connection between glycosylation and disease. Objective: The aim of the present study was to investigate whether certain single nucleotide polymorphisms (SNPs) in genes encoding glycosyltransferases and glycosidases could be associated with elevated risk for chronic obstructive pulmonary disease (COPD) and lung adenocarcinoma. Methods: A total of 32 SNPs localized in genes related to N-glycosylation were selected for the association analysis. Polymorphisms with putative biological functions (missense or regulatory variants) were recruited. SNPs were genotyped by a TaqMan OpenArray platform. A single base extension-based method in combination with capillary gel electrophoresis was used for verification. Results: The TaqMan OpenArray approach provided accurate and reliable genotype data (global call rate: 94.9%, accuracy: 99.6%). No significant discrepancy was detected between the obtained and expected genotype frequency values (Hardy–Weinberg equilibrium) in the healthy control sample group in case of any SNP confirming reliable sampling and genotyping. Allele frequencies of the rs3944508 polymorphism localized in the 3’ UTR of the MGAT5 gene significantly differed between the sample groups compared. Conclusion: Our results suggest that the rs34944508 SNP might modulate the risk for lung cancer by influencing the expression of MGAT5. This enzyme catalyzes the addition of N-acetylglucosamine (GlcNAc) in beta 1-6 linkage to the alpha-linked mannose of biantennary N-linked oligosaccharides, thus, increasing branching that is the characteristic of invasive malignancies.
Keywords: capillary gel electrophoresis